Highly soluble 7-oxy-3-(4-methoxyphenyl)coumarin bearing zinc phthalocyanines: Synthesis and investigation of photophysical and photochemical properties - (:unkn) unknown (ELSEVIER SCIENCE SA, 2011)
The synthesis of 7-oxy-3-(4-methoxyphenyl)coumarin-substituted peripherally and non-peripherally tetrakis- and peripherally octakis-tetrachloro zinc(II) phthalocyanine complexes are described for the first time in this study. The new compounds have been characterized by elemental analysis, IR, (1)H NMR, UV-vis spectroscopy and mass spectra. The photophysical and photochemical properties are important for photodynamic therapy applications and these properties of studied phthalocyanine complexes are investigated in N,N-dimethyl formamide (DMF). The effects of the number of the substitution and the position (peripheral or non-peripheral) on the photophysical and photochemical parameters of the zinc(II) phthalocyanine complexes are reported. The fluorescence quenching behaviour of the studied zinc(II) phthalocyanine complexes by the addition of 1,4-benzoquinone are also described. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Coumarin (2H-chromen-2-one); Zinc; Fluorescence; Quantum yield; Singlet oxygen; SUBSTITUTED PHTHALOCYANINES; PHOTODYNAMIC THERAPY; SPECTROSCOPIC PROPERTIES; MOLECULAR MATERIALS; ANTITUMOR-ACTIVITY; DIMER FORMATION; THIN-FILMS; COUMARIN; AGGREGATION; PORPHYRINS